1995
DOI: 10.1111/j.1532-5415.1995.tb05809.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Alcohol Use Disorders in the Nursing Home

Abstract: The prevalence of lifetime alcohol abuse and dependence was high in this VA NH population. Both the CAGE and MAST-G are sensitive to AUDs in this setting. The areas under the ROC curves were not significantly different and indicate both tests discriminated well between NH residents with and without AUDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
2
1

Year Published

1996
1996
1998
1998

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 24 publications
(13 reference statements)
5
25
2
1
Order By: Relevance
“…Our results con®rm the UK ®ndings of Naik et al (1995) and Mangion et al (1992) that the CAGE is an ineective screening instrument for older UK inpatients, but appear to con¯ict with the USA ®ndings of Buchsbaum et al (1992) and Joseph et al (1995), who found the CAGE to have satisfactory sensitivities of 0.70 and 0.82 respectively. Beresford suggests that the sensitivity of the CAGE drops o rapidly for people aged 80 and above (Beresford, 1993) and this may explain the seemingly contradictory results.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Our results con®rm the UK ®ndings of Naik et al (1995) and Mangion et al (1992) that the CAGE is an ineective screening instrument for older UK inpatients, but appear to con¯ict with the USA ®ndings of Buchsbaum et al (1992) and Joseph et al (1995), who found the CAGE to have satisfactory sensitivities of 0.70 and 0.82 respectively. Beresford suggests that the sensitivity of the CAGE drops o rapidly for people aged 80 and above (Beresford, 1993) and this may explain the seemingly contradictory results.…”
Section: Discussionsupporting
confidence: 75%
“…American studies indicate that the CAGE is a sensitive and speci®c screen for alcohol misuse in older people (Buchsbaum et al, 1992;Joseph et al, 1995). In contrast, UK studies, although indicating that it is a sensitive screening instrument in younger volunteers (Wallace and Haines, 1985;King, 1986), ®nd the CAGE to have a low sensitivity (0±0.19) in older patients (Naik et al, 1995;Mangion et al, 1992).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Despite these concerns, among older adults without cognitive impairment, several studies have demonstrated that alcohol use histories can be reliably obtained (Blow, 1993;Buchsbaum, 1992;Joseph, 1995;Longnecker, 1992). Several standardized screening instruments such as the CAGE or the MAST-G have been found to be reliable and valid in identifying patients with alcohol use disorders both lifetime and current (Blow, 1993;Buchsbaum, 1992;Joseph, 1995).…”
Section: Obtaining Clinical Historymentioning
confidence: 97%
“…Several standardized screening instruments such as the CAGE or the MAST-G have been found to be reliable and valid in identifying patients with alcohol use disorders both lifetime and current (Blow, 1993;Buchsbaum, 1992;Joseph, 1995). Standardized methods that obtain information regarding lifetime alcohol use and problems related to alcohol include quantity and frequency questionnaires and instruments such as the Semi Structured Assessment for the Genetics of Alcoholism (SSAGA) or the Drinking Problems Index (Bucholz, 1994;Finney, 1991).…”
Section: Obtaining Clinical Historymentioning
confidence: 99%